Perlindungan hukum anak buah kapal dalam aspek kesejahteraan di bidang hukum ketenagakerjaan - Azis Prama Pramuditya; Agus Mulya Karsona; Holyness Singadimedja (University of Merdeka Malang, 2020)
Seafarers is one of the profession of maritime sector that play most important roles in shipping activity in Indonesia. Due to the unpredictability of weather, mightiness of the sea and other unpredictable factors made the work of seafarers full of risk. The risk of seafarers profession made anyone who works on the sea should be protected. Thus, there should be seafarers employment agreement between the shipowner and the seafarers. The main purpose of this study is to find out the legal protection of seafarer since the agreement concluded until the end of the employment agreement and also to know what the legal action that can be done by seafarer if one of its rights is not fulfill so they can not reach their welfare. This study is based on juridis-normative approaach that use primary and secondary data sources. The result of this study shows that remuneration aspect, sosial benefits and mechanism of employment termination factors are so important to determine seafarers walfare. Based on on the reasearch, dispute between the employment and the employer can be solved in industial relations court.How to cite item: Pramuditya, A., Karsona, A., Singadimedja, H. (2020). Perlindungan hukum anak buah kapal dalam aspek kesejahteraan di bidang hukum ketenagakerjaan. Jurnal Cakrawala Hukum, 11(2), 136-146. doi:https://doi.org/10.26905/idjch.v11i2.4100